Research progress on delayed flowering under short-day condition in Arabidopsis thaliana - Wang, Yunhui; Lv, Tianxiao; Fan, Tian; Zhou, Yuping; Tian, Chang-en (Frontiers in Plant Science, 2025)
Flowering represents a pivotal phase in the reproductive and survival processes of plants, with the photoperiod serving as a pivotal regulator of plant-flowering timing. An investigation of the mechanism of flowering inhibition in the model plant Arabidopsis thaliana under short-day (SD) conditions will facilitate a comprehensive approach to crop breeding for flowering time, reducing or removing flowering inhibition, for example, can extend the range of adaptation of soybean to high-latitude environments. In A. thaliana, CONSTANS (CO) is the most important component for promoting flowering under long-day (LD) conditions. However, CO inhibited flowering under the SD conditions. Furthermore, the current studies revealed that A. thaliana delayed flowering through multiple pathways that inhibit the transcription and sensitivity of FLOWERING LOCUS T (FT) and suppresses the response to, or synthesis of, gibberellins (GA) at different times, for potential crop breeding resources that can be explored in both aspects. However, the underlying mechanism remains poorly understood. In this review, we summarized the current understanding of delayed flowering under SD conditions and discussed future directions for related topics.